APPLICATION OF THE MRP CONCEPT FOR SMALL INDUSTRIES: implementing material planning - Afonso, Igor Henrique; Jose Bertaci, Moacir (Revista Interface Tecnológica, 2021)
It has been seen that with the increase in the demand of the industries, the productive processes of the companies need to be more and more planned and controlled so that the productive flow is more and more efficient and effective, making this way to reach high levels of productivity, through well-defined processes and plans for optimization of physical space and process losses. Thus, this article aims to study the implementation of the MRP process in a company located in the city of Matão, which has a production process with an infinity of materials necessary to produce a single finished product, which increases the complexity of the planning as a whole. The study presents concepts through monographs, books, and websites, as well as the experience through the production process to adapt the concepts to the process. A process that did not exist in the company was carried out and designed and put into practice, based on the company’s needs to have a delivery control, and a rigorous adjustment in the physical capacity of the stock. With this, the ideal scenario was reached in which the inventory volumes were adjusted, and the deliveries started not to overload the company’s receipts, in addition to maintaining total control of deliveries centralized in the PCP sector.